Islamic Legal Review of the Sale and Purchase of Joint Property Post-Divorce Based on Compilation of Islamic Law - Devi Agustiana; Kurniawan; Zeni Sunarti; Daud; Alisyah Pitri; Kuswanto (Zabags Qu Publish, 2026)
This study analyzes the sale and purchase of joint property following divorce in Jatimulyo Village from the perspective of Islamic law and the Compilation of Islamic Law. The issue is significant because field practices frequently diverge from formal Islamic norms and statutory requirements. Employing a qualitative phenomenological approach, the research explores the lived experiences, perceptions, and meanings held by transaction participants through in-depth interviews, field observation, and document review. Findings indicate that the community regards joint property as assets accumulated during marriage that may be sold after divorce provided mutual agreement exists; transactions are typically conducted through deliberation, trust-based arrangements, and are morally endorsed by village officials and religious leaders. Substantively, these practices align with core muamalah principles justice, consent, and clarity of contract yet they often lack full compliance with Compilation of Islamic Law’s administrative requisites that emphasize formal, written consent. The results suggest a pragmatic harmonization between sharia values and local customs and highlight the need to strengthen legal literacy on Islamic property law and to improve village-level administrative mechanisms to secure legal certainty. This study contributes empirically to Islamic family law and applied muamalah scholarship in rural contexts.